Nekateri filozofski vidiki staranja v kontekstu športa - Pisk, Jernej (Šport (Ljubljana), 2024)
Few people know how to be old. Many waste their time in old age, and wait for time to waste them. Does old age also require its own knowledge, have its own wisdom? In this article we will look at some of the dilemmas of ageing, what selected philosophers have to say about old age, and how this can be related to the physical activity of older adults. As we age, the body becomes the focus of interest. In relation to physical changes and limitations, dilemmas arise concerning autonomy and personal identity. We will touch upon the discourse of »successful old age«, and the moralising of those who may not have been lucky enough in the lottery of life to meet the criteria of a created normality. We will then turn to some of the major philosophers of antiquity. We will see that their understanding of old age was in many ways different from the prevailing one today, but that does not mean that they have nothing to say to us. On the contrary: they repeatedly recognised the advantage of old age, especially from the point of view of liberating the soul (mind, consciousness) from the demands of the body. We conclude this article with the thought that »successful ageing « is a complex concept that cuts across many different areas. Therefore, only the most holistic approach can lead to the desired conclusion that life is (was) good.
Keywords: age; aging; autonomy; avtonomija; body; identiteta; identity; modrost; sport; staranje; starost; šport; telo; wisdom